Magnetic Resonance Imaging in Ophthamology - Fanea, Laura; Fagan, Andrew J (My University, 2012)
Imaging the eye with magnetic resonance imaging (MRI) has proved difficult due to the eye?s propensity to move involuntarily over typical imaging timescales, obscuring the fine structure in the eye due to the resulting motion artifacts. However, advances in MRI technology help to mitigate such drawbacks, enabling the acquisition of high spatiotemporal resolution images with a variety of contrast mechanisms. This review aims to classify the MRI techniques used to date in clinical and preclinical ophthalmologic studies, describing the qualitative and quantitative information that may be extracted and how this may inform on ocular pathophysiology.
PUBLISHED
Keywords: Occular MRI; Ophthamology